Evaluation and suitability of a biomaterial as oil-based drilling fluids viscosifier using chemical structural properties approach - Uwaezuoke, Nnaemeka; C. Igwilo, Kevin; Oguamah, Ifeanyi; C. Samuel, George (International Journal of Engineering and Technology, 2022)
Mucuna solannie is a locally sourced material in Nigeria and other parts of Africa that enhances the viscosity of a drilling fluid. Due to its effectiveness, studies have been carried out on the structural properties of its seed flour for suitability as additive in oil-base mud. The chemical structures, name and other physiochemical properties of Mucuna solannie were determined using X-Ray Diffraction method, and the Fourier Transform Infrared Spectrometer. The scanned sample of Mucuna solannie was used to confirm the molecular bonding form, chemical structures and certain functional groups as basis of spectrum type. The result showed that Mucuna solannie was close to chitosan with covalent bonded molecular structure having calcium salt alone. It is a crystalline polymer and would require high calorific value to break the bonding energy existing in the molecules. Then, the FTIR discovered some functional groups and the position of carbon-carbon, carbon-hydrogen indicating the double bond.Â Â